Structure and conductivity enhanced treble-shelled porous silicon as an anode for high-performance lithium-ion batteries. Issue 61 (1st November 2019) - Lin, Yangfan; Lin, Hanqing; Jiang, Jingwei; Yang, Deren; Du, Ning; He, Xueqin; Ren, Jianguo; He, Peng; Pang, Chunlei; Xiao, Chengmao
Abstract : In this paper, a treble-shelled porous silicon structure is synthesized through three-step approach to enhance the structural stability and conductivity. Abstract : Silicon is regarded as the next generation anode material for lithium-ion batteries because of its high specific capacity, low intercalation potential and abundant reserves. However, huge volume changes during the lithiation and delithiation processes and low electrical conductivity obstruct the practical applications of silicon anodes. In this study, a treble-shelled porous silicon (TS-P-Si) structure was synthesized via a three-step approach. The TS-P-Si anode delivered a capacity of 858.94 mA h g −1 and a capacity retention of 87.8% (753.99 mA h g −1 ) after being subjected to 400 cycles at a current density of 400 mA g −1 . The good cycling performance was due to the unique structure of the inner silicon oxide layer, middle silver nano-particle layer and outer carbon layer, leading to a good conductivity and a decreased volume change of this silicon-based anode.